Studies on the bioactivities of selected Eastern Cape seaweeds - Carter, Anne Margaret (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1994)
In studies on the bioactivities of selected eastern Cape seaweeds, a suitable extraction solvent, namely methanol was used. The antimicrobial, antineoplastic and antiviral activities were investigated, and a seasonal comparison of antimicrobial activities as well as a scanning electron microscopic study were included. A number of algae were found to display significantly high antibacterial activities, of these, the two red algae Plocamium corallorhiza and Laurencia glomerata and the two brown algae Zonaria subarticulata and Ecklonia biruncinata showed the most potent broad spectrum antibacterial activity. L.glomerata and E.biruncinata were active against all five test bacteria, but were inactive against the yeast Candida albicans. C.albicans was the most resistant organism tested,~with only Peyssonelia capensis, f-corallorhiza and Ulva rigida inhibiting its growth. Of the 17 seaweeds tested, none showed any clear seasonal changes in antimicrobial activity. The microorganisms however did vary in their susceptibility to treatment. Staphylococcus aureus and the Micrococcus species were the most susceptible to treatment by the algal extracts, with the Gram positive endospore former, Bacillus subtilis and the two Gram negative bacteria Escherichia coli and Pseudomonas aeruginosa showing more resistance to treatment. C.albicans however was the most resistant organism. In the antineoplastic studies, the brown algae Z.subarticulata, E.biruncinata and Sargassum heterophyllum showed potent activity against both the normal, LLCMK, and cancerous, mouse melanoma-3S0 cells, reducing cell growth in each case. The green algae showed potent activity against the cancerous cells, lowering growth to 30% that of the normal cells. Normal cell growth was unaffected or was stimulated by the presence of these algal extracts. The red algae showed no antineoplastic activity. Representatives of each of the red, brown and green algae were used in the brine shrimp (Artemia salina) cytotoxicity study. None of the algae showed any toxicity towards the brine shrimp. In the antiviral studies against Polio Type 1, strain L-Sa, a reduction in virus infectivity was used as an indication of the presence of antiviral properties in the seaweeds tested. This was done by comparing the virus titres of algal-treated cells with those of untreated cells. Six of the algae tested displayed antiviral activity, these were the two Rhodophyceae Hypnea spicifera and L.glomerata, the two Phaeophyceae Dictyopteris macrocarpa and Dictyota naevosa, and the two Chlorophyceae U.rigida and Halimeda cuneata. Of these, D.naevosa showed particularly strong activity, recording a log reduction in virus titre of 4.
Keywords: Marine algae -- South Africa -- Eastern Cape; Marine algae